Landau gauge Yang-Mills correlation functions - Cyrol, Anton Konrad; Mitter, Mario; Pawlowski, Jan M.; Strodthoff, Nils (Physical review, 2016)
We investigate Landau gauge SU(3) Yang-Mills theory in a systematic vertex expansion scheme for the effective action with the functional renormalization group. Particular focus is put on the dynamical creation of the gluon mass gap at nonperturbative momenta and the consistent treatment of quadratic divergences. The nonperturbative ghost and transverse gluon propagators as well as the momentum-dependent ghost-gluon, three-gluon and four-gluon vertices are calculated self-consistently with the classical action as the only input. The apparent convergence of the expansion scheme is discussed and within the errors, our numerical results are in quantitative agreement with available lattice results.
Gesehen am 30.11.2017